Analisis Faktor - Faktor Yang Mempengaruhi Indeks Pembangunan Manusia (IPM) Di Kota Surakarta Tahun 2015-2022 - Mahendra Tama, Thoriq Wahyu; Hasmarini, Maulidyah Indira (JURNAL ILMIAH EDUNOMIKA, 2024)
Purpose: analyze the effect of the variables number of employment, unemployment rate and regional minimum wage on the human development index. Methodology: The analysis method in this study is econometric analysis of panel data regression from 2015 to 2028 in Surakarta City, in Central Java Province using e-Views software. Results: The results of the study on the partial test (t-test) explained that there was a positive and significant influence on the number of jobs and regional minimum wages on the human development index, but on the variable unemployment rate there was a negative and significant influence on the human development index in Surakarta City in the 2015-2022 period. Applications/Originality/Value: This study is different from the previous one where adding or using the level of unemployment and employment as independent variables against variables bound to the human development index in Surakarta City, Central Java Province